1993
DOI: 10.1113/jphysiol.1993.sp019702
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between central pattern generators for breathing and swallowing in the cat.

Abstract: SUMMARY1. We examined the interaction between central pattern generators for respiration and deglutition in decerebrate, vagotomized, paralysed and ventilated cats (n = 10), by recording activity from the following nerves: hypoglossal, phrenic, thyroarytenoid and triangularis sterni. Fictive breathing was spontaneous with carbon dioxide above the apnoeic threshold (end-tidal Pco2, 32 + 4 mmHg) and fictive swallowing was induced by stimulating the internal branch of the left superior laryngeal nerve (SLN) conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 35 publications
3
93
2
Order By: Relevance
“…At present there is insufficient evidence to make a clear choice between these possibilities, or to suggest that both are involved. However, corticofugal inputs are not required because swallowing in decerebrate animals is associated with normal alterations in respiratory timing (Miller & Sherrington, 1916;Hukuhara & Okada, 1956;Sumi, 1963;Altschuler, Davies & Pack, 1987;Dick et al 1993). Airflow changes during deglutition Deglutition was associated with a characteristic sequence of oronasal airflow changes: (1) rapid decrease in airflow;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present there is insufficient evidence to make a clear choice between these possibilities, or to suggest that both are involved. However, corticofugal inputs are not required because swallowing in decerebrate animals is associated with normal alterations in respiratory timing (Miller & Sherrington, 1916;Hukuhara & Okada, 1956;Sumi, 1963;Altschuler, Davies & Pack, 1987;Dick et al 1993). Airflow changes during deglutition Deglutition was associated with a characteristic sequence of oronasal airflow changes: (1) rapid decrease in airflow;…”
Section: Discussionmentioning
confidence: 99%
“…The neural signal that links the initiation of swallowing with alterations in respiratory rhythm has not been characterized. Two broad explanations are that: (1) activation of the deglutitive pattern generator within the brainstem in turn causes alteration in rhythm-generating respiratory neurones (Dick, Oku, Romaniuk & Cherniack, 1993); or (2) pathways that facilitate the deglutitive neural generator, such as SLN, corticofugal fibres, and relay sites such as the NTS, cause parallel alterations in respiratory rhythm-generating neurones, without direct influences of the deglutitive generator. At present there is insufficient evidence to make a clear choice between these possibilities, or to suggest that both are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of innate sensori primitives include visual movement detection and tracking systems (Bronson, 1974), basic human facial expression perception (Johnson, 2001;Meltzoff and Moore, 1977), or special auditory filters tuned for speech processing in humans (Sekuler and Blake, 1994). Examples of motor primitives include central pattern generators such as for leg oscillations (Cazalets et al, 1995), synergies for reaching with the hand (d 'Avella et al, 2006), closing the fingers in a coordinated manner such as used in grasping (Weiss and Flanders, 2004), or of course skills such as breathing or swallowing (Dick et al, 1993). Of course, the existence of these primitives does not avoid the fundamental need for learning, even for the most basic skills: those primitives are typically parameterized, and thus can typically be seen as parameterized dynamical systems which semantics (affordances in particular), parameter values to be set and combination for achieving given tasks have to be learnt.…”
mentioning
confidence: 99%
“…The expiratory phase is known to predominate during swallowing in both intact and decerebrate feline models (Dick et al, 1993;Doty & Bosma, 1956). …”
Section: Discussionmentioning
confidence: 99%
“…With normal adults, the E-E pattern dominates during a swallow (Martin-Harris et al, 2005;Martin-Harris, Brodsky, Price, Michel, & Walters, 2003), meaning air flows out of the system before and after a swallow. Studies with anaesthetized (Doty & Bosma, 1956) or decerebrated (Dick, Oku, Romaniuk, & Cherniack, 1993) cats have reported that the E-E phase predominates during swallowing.…”
Section: Swallowing and Respiratory Patterns Following Hnc Treatmentmentioning
confidence: 99%